The Development and Psychometric Properties of the Visuospatial Working Memory Assessment (VWMA) for Children. (1st April 2020) - Wangkawan, Thitiya; Lai, Cynthia; Munkhetvit, Peeraya; Yung, Trevor; Chinchai, Supaporn
Abstract : The visuospatial working memory plays a crucial role in the occupational performance of children including daily living and academic achievement. Unfortunately, relevant visuospatial working memory tests in the occupational therapy setting are lacking. Therefore, it is of clinical interest to develop new assessment tools in this area. The present study is aimed at summarizing the development of the visuospatial working memory assessment (VWMA) and assessing its psychometric properties. The results revealed that the score of item-objective congruence index (IOC) was 1.0 in overall items of assessment. The Cronbach alpha test confirmed that the internal consistency of VWMA showed good reliability in both types of the assessment, with the total score of computerized tests being .88 and the tabletop tests being .81. The computerized test was found to have excellent test-retest reliability with intraclass correlation coefficient (ICC) values ranging from .88 to .99. The tabletop test was found to have a fair to good test-retest reliability with the ICC values ranging from .51 to .63. As regards construct validity, the results revealed that the tasks in the computerized test identified a significant difference between the control group, normal children, and children with attention deficit/hyperactivity disorder (ADHD) group. The exception to this was the N -back task in which the independent sample t -test of computerized test ranged from 1.61 to 6.23. The results of the tabletop test revealed a significant difference between normal children and the children in the ADHD group over all tasks in which the independent sample t -test ranged from 3.05 to 8.40. In conclusion, good psychometric properties established as regards content validity, internal consistency, test-retest reliability, and construct validity provide evidence to support the position that the new VWMA is appropriate for children.